2007
DOI: 10.1042/cs20070238
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of respiratory muscle function in pulmonary hypertension

Abstract: It has been suggested that impaired respiratory muscle function occurs in patients with PH (pulmonary hypertension); however, comprehensive investigations of respiratory muscle function, including the application of non-volitional tests, needed to verify impairment of respiratory muscle strength in patients with PH have not yet been performed. In the present study, respiratory muscle function was assessed in 31 patients with PH (20 females and 11 males; mean pulmonary artery pressure, 51+/-20 mmHg; median Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 41 publications
6
84
1
6
Order By: Relevance
“…1) and the identical Poes,sniff values pre-and post-exercise in both PAH-H and PAH-NH patients. Differences in technique and disease stage/severity between our PAH population and those of other studies [14][15][16] may explain the differences between our results and those of other studies.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…1) and the identical Poes,sniff values pre-and post-exercise in both PAH-H and PAH-NH patients. Differences in technique and disease stage/severity between our PAH population and those of other studies [14][15][16] may explain the differences between our results and those of other studies.…”
contrasting
confidence: 57%
“…Although inspiratory muscle dysfunction has been suspected in PAH patients at rest [14,15], mostly in severely compromised PAH attending for pulmonary transplantation [16], the contribution of inspiratory muscle weakness/fatigue to the decreased IC can reasonably be ruled out in our PAH-H patients: inspiratory muscle strength was preserved, as highlighted by the preserved Poes,IC during CPET ( fig. 1) and the identical Poes,sniff values pre-and post-exercise in both PAH-H and PAH-NH patients.…”
mentioning
confidence: 99%
“…More recently, several reports suggested muscle dysfunction in patients with pulmonary arterial hypertension [14][15][16]. Mechanisms are still unclear, but it can be speculated that inactivity of the skeletal muscles, together with a decreased cardiac output leading to a reduced oxygen transport to the skeletal muscles, trigger morphological changes, such as muscle atrophy, fibre type switching and reduced aerobic capacity [18].…”
Section: Training Improved Endurance Capacitymentioning
confidence: 99%
“…Respiratory muscle dysfunction was found in two studies, both by voluntary and nonvoluntary techniques [14,15]. More recently, forearm muscle dysfunction has been reported in these patients [16].…”
mentioning
confidence: 99%
“…Another experimental study evaluated changes in contractile performance, diaphragm morphology, and inspiratory muscle weakness in rats with PH, and revealed that these rats had a significant reduction in the diaphragm's maximal contraction and generation forces. As this weakness appears to be specific to the diaphragm muscle, rather than generalized weakness, it is possible that chronic activity of the diaphragm can be triggered in cases of PH 11,12 .…”
Section: Tablementioning
confidence: 99%